Rebels: youth and the Cold War origins of identity - Medovoi, Leerom (New Americanists, 2005)
Identitarian thought and the Cold War world -- Cold War literature and the national allegory : the identity canon of Holden Caufield -- Transcommodification : rock-n-roll and the suburban counterimaginary -- Identity hits the screen : teenpics and the boying of rebellion -- Oedipus in suburbia : bad boys and the Fordist family drama -- Beat fraternity and the generation of identity -- Where the girls were : figuring the female rebel -- Conclusion : the rise and fall of identity.